Effect of Length, Diameter, Chirality, Deformation, and Strain on Contact Thermal Conductance Between Single-Wall Carbon Nanotubes - Varshney, Vikas; Lee, Jonghoon; Brown, Joshua S.; Farmer, Barry L.; Voevodin, Andrey A.; Roy, Ajit K. (Frontiers in Materials, 2018)
Thermal energy transfer across physically interacting single-wall carbon nanotube (SWCNT) interconnects has been investigated using non-equilibrium molecular dynamics simulations. The role of various geometrical and structural (length, diameter, chirality) as well as external (deformation and strain) carbon nanotube (CNT) parameters has been explored to estimate total as well as area-normalized thermal conductance across cross-contact interconnects. It is shown that the CNT aspect ratio and degree of lateral as well as tensile deformation play a significant role in determining the extent of thermal energy exchange across CNT contacts, while CNT chirality has a negligible influence on thermal transport. Depending on the CNT diameter, aspect ratio, and degree of deformation at the contact interface, the thermal conductance values can vary significantly –by more than an order of magnitude for total conductance and a factor of 3 to 4 for area-normalized conductance. The observed trends are discussed from the perspective of modulation in number of low frequency out-of-plane (transverse, flexural, and radial) phonons that transmit thermal energy across the contact and govern the conductance across the interface. The established general dependencies for phonon governed thermal transport at CNT contacts are anticipated to help design and performance prediction of CNT-based flexible nanoelectronic devices, where CNT-CNT contact deformation and strain are routinely encountered during device operations.